Implementation of The Role of Teachers in Inclusive Education at MTs Generasi Emas Denpasar - Wahyu Sihab; Desvita Rizki Ramadhanty (Asosiasi Ilmuwan Pendidikan, Sosial, dan Humaniora Indonesia, 2026)
Inclusive education in the context of Islamic religious education reflects the implementation of Islamic values that promote respect for diversity and the protection of individual rights. Islamic Religious Education teachers play a crucial role in ensuring that all students, including those with special needs in inclusive schools, can access and understand Islamic teachings at the Madrasah Tsanawiyah level. Inclusive education also functions as a catalyst for educational transformation by promoting equality and fairness in the learning process without discrimination among students. In this context, teachers are required to adapt teaching strategies, learning materials, and classroom interactions according to the diverse needs and abilities of each learner. Their role is not only to deliver religious knowledge but also to foster an inclusive learning environment that supports participation and understanding for all students. This study contributes to a deeper understanding of the role of Islamic Religious Education teachers within inclusive education settings and provides insights that may support future research and development of inclusive education practices in Indonesia.